Rhetoric of the Advertising Audience – A Facebook Ad as a Model - ammari, azzeddine (El Omda in Linguistics and Discourse Analysis, 2019)
If classical rhetoric focused on the eloquence of speech (the discourse) and the speaker (the orator), paying little attention to the receiver or the audience, a new rhetorical direction has emerged that places the listener at the center, emphasizing the reception of the discourse by the individual. This approach, now known as “audience rhetoric,” has been adopted and applied by many researchers to various aspects of private and public life. Credit for this trend is often given to the Egyptian scholar Imad Abdel Latif. From this perspective, the present study aims to introduce this approach by applying it to a Facebook advertisement for the telecommunications company Ooredoo Algeria. The study investigates the rhetoric of the audience on this type of social network by observing, classifying, and analyzing users’ comments, with the aim of addressing key questions. These questions primarily concern the audience’s interest in advertising